Increasing Hauler Productivity with Fleet Management System and Application to Mining Operational Safety of Pt. Antareja Mahada Makmur - Iyanta Destian Sitorus; Rony Gunawan; Muhammad Iqbal Syaf Rizal; Milzam Khisnul Askhar (Publikasi Indonesia, 2024)
This research aims to increase the productivity of hauler units at PT Antareja Mahada Makmur (PT AMM) through the implementation of Fleet Management System (FMS) and operational safety management. Coal hauling is a vital transportation activity in the mining industry, but it often experiences obstacles in achieving productivity targets. Using a descriptive method, the study identifies the root causes of issues affecting productivity and safety, including a lack of digital monitoring systems and operators' understanding of productivity targets. The implementation of FMS enables real-time monitoring of driving behavior, reduction of unproductive time, and increased control over operator safety. The results of the evaluation showed an increase in the productivity of the hauler unit from 13.7 tons/hour to 14.2 tons/hour, as well as a decrease in Empty Stop Time (EST) by 38%. In addition, the system also contributes to the reduction of incidents due to operator fatigue. The study concluded that the implementation of FMS not only increases productivity, but also strengthens operational safety, having a positive impact on worker quality, cost, and morale.